Accuracy of applicator tip reconstruction in MRI-guided interstitial 192Ir-high-dose-rate brachytherapy of liver tumors. Issue 1 (April 2015) - Wybranski, Christian; Eberhardt, Benjamin; Fischbach, Katharina; Fischbach, Frank; Walke, Mathias; Hass, Peter; Röhl, Friedrich-Wilhelm; Kosiek, Ortrud; Kaiser, Mandy; Pech, Maciej; Lüdemann, Lutz; Ricke, Jens
Abstract: Background and purpose: To evaluate the reconstruction accuracy of brachytherapy (BT) applicators tips in vitro and in vivo in MRI-guided 192 Ir-high-dose-rate (HDR)-BT of inoperable liver tumors. Materials and methods: Reconstruction accuracy of plastic BT applicators, visualized by nitinol inserts, was assessed in MRI phantom measurements and in MRI 192 Ir-HDR-BT treatment planning datasets of 45 patients employing CT co-registration and vector decomposition. Conspicuity, short-term dislocation, and reconstruction errors were assessed in the clinical data. The clinical effect of applicator reconstruction accuracy was determined in follow-up MRI data. Results: Applicator reconstruction accuracy was 1.6 ± 0.5 mm in the phantom measurements. In the clinical MRI datasets applicator conspicuity was rated good/optimal in ⩾72% of cases. 16/129 applicators showed not time dependent deviation in between MRI/CT acquisition ( p > 0.1). Reconstruction accuracy was 5.5 ± 2.8 mm, and the average image co-registration error was 3.1 ± 0.9 mm. Vector decomposition revealed no preferred direction of reconstruction errors. In the follow-up data deviation of planned dose distribution and irradiation effect was 6.9 ± 3.3 mm matching the mean co-registration error (6.5 ± 2.5 mm; p > 0.1). Conclusion: Applicator reconstruction accuracy in vitro conforms to AAPM TG 56 standard. Nitinol-inserts are feasible for applicator visualization and yield good conspicuity in MRI treatment planning data. No preferred direction of reconstruction errors were found in vivo.